Anti/pro/critical porn studies - Smith, Clarissa; Attwood, Feona (Porn Studies, 2014)
In this introductory article we explore contemporary debates about the ‘critical’ study of pornography in relation to ‘anti-porn’, ‘pro-porn’, ‘sex-positive’ and ‘sex-critical’ approaches, and the recent reframing of pornography and sex more generally in relation to postfeminism and neoliberalism. The article reviews emerging work in porn studies, discusses the importance of developing a critical examination of the porn industries, and introduces the contributions that comprise this first issue. We end with some thoughts on nomenclature.
Keywords: communication; cours; discipline; premier cycle; sex1911; sexualité; thématiques; études culturelles; études pornographiques